The Effect of Different Rhizobial Symbionts on the Composition and Diversity of Rhizosphere Microorganisms of Chickpea in Different Soils - Zhang, Junjie; Wang, Nan; Li, Shuo; Wang, Jingqi; Feng, Yufeng; Wang, Entao; Li, Youguo; Yang, Tao; Chen, Wenfeng (Plants (Basel), 2023)
Background: Chickpea (Cicer arietinum L.) is currently the third most important legume crop in the world. It could form root nodules with its symbiotic rhizobia in soils and perform bio-nitrogen fixation. Mesorhizobium ciceri is a prevalent species in the world, except China, where Mesorhizobium muleiense is the main species associated with chickpea. There were significant differences in the competitive ability between M. ciceri and M. muleiense in sterilized and unsterilized soils collected from Xinjiang, China, where chickpea has been grown long term. In unsterilized soils, M. muleiense was more competitive than M. ciceri, while in sterilized soils, the opposite was the case. In addition, the competitive ability of M. ciceri in soils of new areas of chickpea cultivation was significantly higher than that of M. muleiense. It was speculated that there might be some biological factors in Xinjiang soils of China that could differentially affect the competitive nodulation of these two chickpea rhizobia. To address this question, we compared the composition and diversity of microorganisms in the rhizosphere of chickpea inoculated separately with the above two rhizobial species in soils from old and new chickpea-producing regions. Results: Chickpea rhizosphere microbial diversity and composition varied in different areas and were affected significantly due to rhizobial inoculation. In general, eight dominant phyla with 34 dominant genera and 10 dominant phyla with 47 dominant genera were detected in the rhizosphere of chickpea grown in soils of Xinjiang and of the new zones, respectively, with the inoculated rhizobia. Proteobacteria and Actinobacteria were dominant at the phylum level in the rhizosphere of all soils. Pseudomonas appeared significantly enriched after inoculation with M. muleiense in soils from Xinjiang, a phenomenon not found in the new areas of chickpea cultivation, demonstrating that Pseudomonas might be the key biological factor affecting the competitive colonization of M. muleiense and M. ciceri there. Conclusions: Different chickpea rhizobial inoculations of M. muleiense and M. ciceri affected the rhizosphere microbial composition in different sampling soils from different chickpea planting areas. Through high throughput sequencing and statistical analysis, it could be found that Pseudomonas might be the key microorganism influencing the competitive nodulation of different chickpea rhizobia in different soils, as it is the dominant non-rhizobia community in Xinjiang rhizosphere soils, but not in other areas.